An Optimal Reconfiguration Strategy of Microgrid Cluster Based on Vulnerability Assessment - LIU Haocheng; DING Xiying (Kongzhi Yu Xinxi Jishu)
The grid-connection of a microgrid group containing of a large number of new energy nodes will cause a decrease in the stability of system operation. This paper presents an optimal reconfiguration strategy of micro-grid cluster based on vulnerability assessment. Firstly, using the simulation operation data of microgrid group under multiple working conditions, the operation state data matrix is constructed based on the measurable variables of each node of the synchronous system, and it is converted into a large number of pictures containing fault information, which is used to train and check the fault identification and classification network based on capsule neural network. On this basis, the influence of various faults on the overall operational stability of a microgrid cluster is analyzed, and the operational vulnerability assessment model of microgrid cluster system is constructed, and the vulnerability assessment of the operational state damage degree of microgrid is carried out based on the fault type identification results. Finally, according to the vulnerability assessment results, the network optimization and reconfiguration of microgrid group are carried out, and for the reconstructed microgrid, the multi-agent consistency control strategy is adopted to optimize the power distribution of the system. Simulation results show that the identification accuracy of five typical faults can reach 98.44%, and the network reconfiguration system based on vulnerability assessment can effectively isolate faults and realize the re-optimization of power distribution.